AGE PECULIARITIES OF THE STRUCTURAL TRANSFORMATIONS IN URINARY BLADDER WALL - Popadynets, O.G. (World of Medicine and Biology, 2012)
The results of morphofunctional condition complex study of the urinary bladder wall structural elements and pro- and antioxidant systems at postnatal ontogenesis stages, this study was performed in the experiment at 20 mature and 20 old-aged male rats. Angioarcitechtonics is in the close relationship with structural-functional peculiarities of the urinary bladder wall in all age periods and these vascular-stromal-tissue transformations run simultaneously and in parallel without homeostasis disturbance. All this associates with the peroxidation processes and antioxidant systems functioning that testify their interrelation and interconditionality and strict control after all the hierarchic regulatory system.
Keywords: urinary bladder; postnatal ontogenesis; mature and old-aged rats